2008
DOI: 10.1103/physrevlett.100.108103
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity in Hydrated Proteins: No Signs of the Fragile-to-Strong Crossover

Abstract: Dielectric spectroscopy studies of hydrated protein demonstrate smooth temperature variations of conductivity. This observation suggests no cusplike fragile-to-strong crossover (FSC) in the protein's hydration water. The FSC at T approximately 220 K was postulated recently on the basis of neutron scattering studies [Chen, Proc. Natl. Acad. Sci. U.S.A. 103, 9012 (2006)] and was proposed to be the main cause for the dynamic transition in hydrated proteins. Following Swenson et al. , we ascribe the neutron result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
118
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(135 citation statements)
references
References 28 publications
16
118
1
Order By: Relevance
“…This was recently suggested for water in different confinements 13 and also experimentally verified for hydrated lysozyme. 37 This study shows that dielectric relaxation does not participate in a FST up to 240 K. A change in fragility should be visible in dielectric relaxation measurements which have been proven to probe reorientational motions better than most other techniques for polar liquids. An inspection of the H diffusivity in ice 38 shows that ice exhibits a very high diffusion rate of water molecules.…”
Section: Apparent Fragile-to-strong Transitionsmentioning
confidence: 74%
“…This was recently suggested for water in different confinements 13 and also experimentally verified for hydrated lysozyme. 37 This study shows that dielectric relaxation does not participate in a FST up to 240 K. A change in fragility should be visible in dielectric relaxation measurements which have been proven to probe reorientational motions better than most other techniques for polar liquids. An inspection of the H diffusivity in ice 38 shows that ice exhibits a very high diffusion rate of water molecules.…”
Section: Apparent Fragile-to-strong Transitionsmentioning
confidence: 74%
“…9 Some of these, or similar confining systems, have also been studied by using other different experimental techniques, such as broadband dielectric spectroscopy (BDS), [10][11][12][13][14][15] nuclear magnetic resonance (NMR), 16 or a combination of different techniques. [17][18][19][20][21][22] In such studies, most likely due to the broadband frequency range analyzed such crossover for water was either not observed, or attributed to other causes different to that of the fragile-to-strong transition scenario. Thus, no correlation was found by studies of the same sample by QENS and other techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Magazù et al [16] and Schirò et al [19] draw opposite conclusions on the role that the dynamic crossover plays in the onset of the PDT with resolution-dependent neutron scattering experiments. Swenson et al [14], Pawlus et al [15], and Fenimore et al [18] propose that the appearance of the dynamic crossover in the hydration water is due to the existences of two different relaxation processes, the structural relaxation and a secondary relaxation, rather than a qualitative * Corresponding author: sowhsin@mit.edu change from an Arrhenius behavior to a super-Arrhenius behavior of the structural relaxation time.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is of particular interest, partially because (i) the crossover temperature T X of the hydration water is close to the transition temperature of the so-called protein dynamic transition (PDT) [13] T D and thus it is conjectured that the PDT is induced by the dynamic crossover of the hydration water [12] and (ii) this crossover is interpreted as an anomalous feature of the structural relaxation of the hydration water and is ascribed to the existence of the high-density liquid and low-density liquid phases in the supercooled water [12]. To date, this phenomenon and its physical implications are still largely debated [14][15][16][17][18][19]. Doster et al [17] state that the crossover observed in Ref.…”
Section: Introductionmentioning
confidence: 99%